Influence of Code of Ethics for Accounting Professional Skills of Auditing and Professionalism of Auditors Towards the Quality of Audit Reports in Point of View the Auditing Service in Bangkok - Chansin, Sasiporn; Sincharoonsak, Titaporn (Mahachula Academic Journal, 2021)
This research aimed to study the accounting professional ethics that affect the quality of audit reports of the auditing service providers. The sample group consisted of 357 people and 318 questionnaires were returned 89.08% by using multiple correlation analysis statistics. The study found that the accounting professional ethics, auditing operational skills and professionalism affected the quality of audit reports from the perspective of auditing service in Bangkok.